Planejamento tributário na jurisprudência do Conselho Administrativo de Recursos Fiscais: desafios de uma pesquisa empírica - Barretto Junior, Valter Pedrosa (2010)
In this paper, we present the conclusions drawn from a research on case law conducted with the Administrative Board for Tax Appeals, through which we could identify some of the characteristics involved in tax-planning transactions that tend to be deemed either legally grounded or groundless against Tax Authorities. Thus, the existence of inconsistent transactions made in a short period of time, combined with the existence of a regular alternative way which proves more burdensome and which may lead to the same results achieved through those transactions made by taxpayers, as well as the existence of related parties, shell companies, fictitious companies, companies domiciled in tax havens, the neutralization of undesired effects, the exercise of unusual transactions and transactions that stray from the purposes of the typical legal businesses involved, are elements that, among others, tend to influence the outcome of cases. We also verified that, in addition to some inconsistencies found, transactions bearing the same characteristics tend to produce the same result as regards the legality of the transactions. However, the legal institutions applied to serve as the basis for such result (such as simulation, abuse of right, business purpose, etc.) vary greatly and present no uniformity. We have found that the institutions themselves, as they have been dealt with in the judgments, were mixed up and no longer find conceptual correspondence with the legal institutes known by scholars. The majority of judgments demonstrated a hybrid institute: a simulation resulting from the inconsistency between the form and its substance and/or resulting from the absence of business purpose. Finally, after having mentioned the characteristics and challenges of the current regulatory model for transactions involving tax planning in our legal system, we have compared the incentives furnished by the possible configurations that can be afforded to the mechanisms that regulate the conducts examined, and we concluded that an enforcement strategy prioritizing the regulation of these conducts based on threatening to adopt severe and unusual penalties is unable to fight the needs of Brazilian reality. Therefore, we understand that a model that prioritizes the capacity to detect infractions, by requiring information transparency and disclosure, and which also avails itself of responsive regulation strategies is the most suitable to serve such needs.